Advances in Biomimetics - Gorb, Stanislav N.; Carbone, Giuseppe; Speck, Thomas; Taubert, Andreas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue presents contributions from biological fields focusing on the identification of underlying principles in living systems, and manuscripts that apply findings obtained from existing systems to modern technologies. We greatly appreciate the time and effort that the Guest Editors devoted to this Special Issue.